Eﬀect of electromagnetic ﬁeld therapy in chronic respiratory disease: systematic review - Jaleel, Ghufran; Khan, R. Abdur; Khan, Ashfaque; Malhotra, Deepak (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Pulmonary function and functional capacity decline in chronic respiratory diseases, especially in chronic obstruc-tive pulmonary disease. Physiotherapy is an integral part of treating respiratory patients since it helps combat muscle deple-tion and respiratory symptoms. Nevertheless, the knowledge about applying electromagnetic ﬁeld (EMF) therapy as a thera-peutic option in chronic respiratory patients is minimal. So, the aim of this review is to determine the eﬀect of Electromagnetic Field Therapy on Pulmonary Function and 6-minute walk distance in chronic respiratory disease patients.Methods. The PubMed, PeDRO, Scopus, COCHRANE, and Web of Science databases were searched and randomised con-trol trials investigating EMF on pulmonary function and 6MWT distance in a chronic respiratory disease population, published before January 2022, were selected. Three reviewers assessed each study’s quality after data were extracted into a trial de-scription form.Results. Three studies met the inclusion criteria on pulmonary function and 6MWT distance. The sample size ranges from 10 to 37 for EMF. The improvement in pulmonary function was not signiﬁcant in FEV1, FEV1/FVC and signiﬁcant in PEF versus control. The change in 6MWT distance was 21.68 m, which is a clinically signiﬁcant change.Conclusions. EMF therapy has been shown to improve pulmonary function and 6MWT distance. The study was the ﬁrst to examine and synthesise existing EMF data.
Keywords: electromagnetic ﬁeld; magnetic stimulation; asthma; chronic obstructive pulmonary disease (COPD); chronic respiratory disease